2013
DOI: 10.1021/ie303555g
|View full text |Cite
|
Sign up to set email alerts
|

Particle Dispersion and Circulation Patterns in a 3D Spouted Bed with or without Draft Tube

Abstract: Solid dispersion and circulation properties in a 3D spouted bed with or without a draft tube are reported based on the CFD-DEM coupling approach. The distribution characteristics of the local and global solid dispersion coefficients are studied. Meanwhile, the effects of tube configuration and bed diameter on these two aspects are investigated. The results show that the large lateral dispersion coefficient concentrates in the spout−annulus interface and the lower part of the fountain region, while the vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…The LES-DEM coupling approach proposed in the current work has been validated with the experimental work of Müller et al (2008) in our previous work Luo et al, 2013aLuo et al, , 2013b). In the model validation, the minimum fluidizing velocity obtained in the experiment has been accurately obtained.…”
Section: Model Validationmentioning
confidence: 79%
See 2 more Smart Citations
“…The LES-DEM coupling approach proposed in the current work has been validated with the experimental work of Müller et al (2008) in our previous work Luo et al, 2013aLuo et al, , 2013b). In the model validation, the minimum fluidizing velocity obtained in the experiment has been accurately obtained.…”
Section: Model Validationmentioning
confidence: 79%
“…The investigated hydrodynamics at two different heights of the system agree well with the experimental data both qualitatively and quantitatively. More details related to the model validation can be found in our previous work Luo et al, 2013aLuo et al, , 2013b. Based on the validation, the coupling model has been applied to investigate the internal transportation mechanisms of solid phase and the tube erosion in the internally circulating fluidized bed Luo et al, 2013aLuo et al, , 2013bYang et al, 2014aYang et al, , 2014b, in which the internal circulation of solid phase is established by introducing a vertical draft tube or a centrally assigned baffle plate in the bubbling fluidized bed.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, spout-fluid beds are more abundant in DEM simulations compared with those performed with TFM, as it can be seen in Table 1 and Section 3.2. A group of researchers from the Zhejiang University employed a geometry with a zig zag wall instead of an inclined one in two different works [103,104] to reproduce the experiments performed in a spouted bed with a conical base by Vieira Neto et al [143].…”
Section: Modelling Based On the Eulerian-lagrangian Approachmentioning
confidence: 99%
“…The circulation of solids within a spouted bed with and without a draft tube was investigated by Luo and colleagues [104] who highlighted the substantial differences observed: the solids dispersion took place in different zones, being more intense when the draft tube is used. They also showed that the extension of the draft tube over the bed surface makes the solid circulation more vigorous.…”
Section: Dem Applied To Auxiliary Devicesmentioning
confidence: 99%